Moderating role of psychological empowerment on the relationship between green HRM practices and millennial employee retention in the hotel industry of Bangladesh - Islam, Md Asadul; Polay, Dieu Hack; Haque, A. K. M. Ahasanul; Rahman, Mahfuzur; Hossain, Md Shahadat (John Wiley & Sons Ltd., 2021)
The purpose of the paper is to examine the relationship between green human resource management (GHRM) practices such as green recruitment, green training, green performance management, green reward, green involvement and millennial employee retention in the hotel industry in Bangladesh. The study examined the moderating effect of psychological empowerment on the relationship between GHRM practices and millennials' retention. This study used a survey questionnaire of 394 employees in Bangladeshi 3-star to 5-star hotels to test hypotheses using SmartPLS. The study found that green reward and green training have significant relationships with millennials' retention in hotels. The results showed psychological empowerment as a significant moderator on the relationship between three GHRM practices, green training, green performance management, green and reward and mil lennials' retention. With significant environmental degradation in South-Asia, this study establishes GHRM can reconcile environmental regeneration and business strategy in the hotel industry, whose environmental footprint is increasingly under scrutiny.